1969
DOI: 10.1172/jci105957
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative relationship of urinary peptide hydroxyproline excretion to collagen degradation

Abstract: A B S T R A C r To determine the quantitative relationship of urinary hydroxyproline peptide excretion to collagen breakdown, known quantities of radioactive hydroxyproline peptides were administered to unlabeled animals and excertion of radioactivity in respiratory carbon dioxide, urine, and feces was measured. The major routes of excretion of collagen peptide metabolites were respiratory carbon dioxide (75%) and urine, as hydroxyproline-containing peptides (25%).Since the predominant urine hydroxyproline pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 24 publications
4
29
0
1
Order By: Relevance
“…24-h urine samples were obtained from 21 untreated subjects with Paget's disease of bone. Five of these subjects were subsequently treated with the diphosphonate disodium etidronate (EHDP) (10) at doses of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] …”
Section: Methodsmentioning
confidence: 99%
“…24-h urine samples were obtained from 21 untreated subjects with Paget's disease of bone. Five of these subjects were subsequently treated with the diphosphonate disodium etidronate (EHDP) (10) at doses of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] …”
Section: Methodsmentioning
confidence: 99%
“…Hydroxyproline is neither specific for bone (9-12) nor for bone resorption (10), moreover it is mostly metabolised before being excreted in urine (13). As a consequence hydroxyproline is a poor bone resorption marker (1).…”
Section: Discussionmentioning
confidence: 99%
“…The organization of collagen may be altered in CP to create a stiffer ECM. Total collagen is measured by assaying for the exclusive collagen-specific modified amino acid hydroxyproline (10). Hydroxyproline is metabolized, excreted, and removed from the lung and kidney.…”
Section: Introductionmentioning
confidence: 99%
“…The other 30% is excreted via the urine. It has been suggested that the ratio of hydroxyproline excreted from the lung to that excreted from the urine is fairly constant; therefore, changes in collagen breakdown can be quantified by measuring the changes in the urine concentration of the prolyl-hydroxyproline peptide, which may reflect ineffective peptidase activity (10,11,12). However, no studies have investigated the correlations between the severity of clinical spasticity, Muscle Hydroxyproline (MH), and Urine Hydroxyproline (UH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation